Singing with Angry Bird - Jee, Hyewon; Kim, Sunah; Jee, Hyewon; Bae, Wonjung; Jee, Hyewon; Won, Sungduk; Song, Wooyong; Vaz, Julian; Song, Joon Seok (South Korea : AUTLOOK Filmsales, 2016)
Jae-Chang Kim is a temperamental Korean opera singer known as Angry Bird. He started a children’s choir in the slums of the Indian city of Pune. The choir changed the lives of children: it gave them self-confidence and structure, and for some, the opportunity to visit Korea. But much to Angry Bird’s frustration, many parents aren’t convinced of the choir’s value. The film follows him as he attempts to organize a joint concert with the parents and their children—a project that often drives him to despair, because parents having trouble making ends meet will always choose work. Nevertheless, music provides a vibrant contrast to life in the slums. It moves both the parents and children, and brings them closer together in the process.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films